Board Game Design for Conservation Organization: A study on the Board Game for Campaign on Indonesian Javan Hawk-Eagle Conservation Foundation - Ardiawan Bagus Harisa; Zahrotul Umami; Filmada Ocky Saputra (Bina Nusantara University, 2022)
A Javan hawk-eagle conservation organization, Yayasan Konservasi Elang Indonesia, is struggling with its marketing & publication activities. The organization then uses a board game to help their conservation works. There are educational and conservative purposes embedded in the game design to be a formal framework to overcome the challenge. Using a board game as a conservation tool engages the players and deepens their understanding of the topic, Javan hawk-eagle. The process we use to develop the framework includes mapping the learning objectives to the game component and actions, board game design steps, and implementation and production of the board game. We then compare the cognitive aspect of the educational goal in a pre-test and post-test of the learners.